The features of control of arterial hypertension in Mongolia (literature review) - T. M. Maksikova (Scientific Сentre for Family Health and Human Reproduction Problems, 2018)
The complications of arterial hypertension cause more than a half of 17 million cases of cardiovascular mortality in the world. According to the official statistics in 2010 Mongolia was the leader among the countries of the Asian Pacific region in mortalityfrom complications connected with arterial hypertension (40.9 people per 100 000 of population). It is proved that lifestyle change with risk factors correction and adequate hypotensive therapy allow to control arterial hypertension in most patients. The real prevalence of the resistant arterial hypertension in the world is less than 10 %. However, in clinical practice even in countries with high income only 50-60 % of persons with arterial hypertension can reach the target blood pressure values less than 140/90 mmHg, in Mongolia, these indicators are worse. Such situation leads to growth of mortality and disability, therefore it is a serious worldwide problem for health care. There are four reasons, which lead to low compliance of patients to be treated: social and administrative problems; medical passivity; irrational therapy and low adherence of patients to recommendations of doctors. But according to different cohort studies, the main reason of poor control of arterial hypertension in Mongolia is insufficient hypotensive therapy, therefore only 23.6 % patients can achieve the target blood pressure values. In such conditions, it is too important to develop a strategy aimed at improving control of arterial hypertension in Mongolia.